The relationship between psychological wellbeing, social support, and personality in an English police force - Jackman, Patricia C. (International journal of police science & management, 2020)
Police employees are exposed to a variety of complex, work-related stressors and are susceptible to experiencing reduced psychological wellbeing. To advance understanding of the personal and social factors underpinning psychological wellbeing in this population, the purpose of this study was to examine the relationship between psychological wellbeing, perceived support from colleagues, received support from colleagues and personality factors in police employees. A sample of 381 police employees from a county police force in England completed an online questionnaire assessing: psychological wellbeing; perceived support; received support; and personality factors. Psychological wellbeing was significantly and positively associated with perceived support from colleagues, received support from colleagues, extraversion, agreeableness, conscientiousness, emotional stability, and openness to experience. Further investigation of these relationships using multiple logistic regression analysis found that perceived support from colleagues, received support from colleagues, extraversion, and emotional stability significantly predicted psychological wellbeing. Given growing concerns about psychological wellbeing in police forces, the findings could help to inform the promotion of psychological wellbeing across operational and non-operational police employees. The results suggest that increasing both perceptions of available support and the amount of support received among employees in police forces is important for enhancing psychological wellbeing in this population. Furthermore, police employees with lower levels of extraversion and emotional stability should also be considered for additional support to promote psychological wellbeing.